Use of Mastodinon in different forms of mastopathy - N. I. Rozhkova; E. V. Meskikh (ABV-press, 2014)
The diffuse benign breast disease mastopathy is most common in reproductive-aged women. According to the World Health Organization, mastopathy is defined as a fibrocystic disease (FCD) characterized by a broad spectrum of proliferative and regressive changes in breast tissues. The prevalence of this disease varies from 30 to 40%. The magnitude of clinical manifestations is highly diverse varying from slight premenstrual tension to the acute pain syndrome accompanied by the higher volume and density of the gland with the formation of nodular proliferations and cysts. In most cases, the present women regard mastopathy as a handicap in daily life and try to resort to sparing therapy options, such as homeopathy or phytotherapy. The phytotherapeutic preparation Mastodinon is one of these pathogenetic effective drugs to treat premenstrual syndrome and FCD. The major active principle is Agnus castus (leban, chaste tree). The clinical efficacy of mastodinon may be judged from the results of a large number of the studies given in this paper.